Typomorfology of building mass and lingkage in Malioboro, Yogyakarta - Indah Pujiyanti; Norainah Abdul Rahman (Penerbit Universiti Kebangsaan Malaysia, 2022)
The Malioboro area of Yogyakarta is one of the main tourist destinations in Yogyakarta, which has the potential for the rapid development of regional structural patterns. Its strategic location in the city center and the presence of historic buildings and first-class shopping centers in the area attract tourists and investors to build in the Malioboro area. On the other hand, Malioboro Street is the philosophical axis of Yogyakarta City which has also been designated as a Cultural Conservation Area. The pattern of regional structure development based on building mass and linkage in this area is the focus of this research. Changes in the Typology of this area were analyzed using a comparative method by comparing data on patterns of building mass and linkage from different 4-year periods. This study aims to find out how the pattern of changes in the typology of buildings in the Malioboro area and its influence on the role of the Malioboro area as a cultural heritage area. Based on the results of the study, it is known that the Typology of building mass and form changes in the Malioboro area there are five types, namely the gradual addition of building mass, the sudden addition, the reduction in building mass (total loss) and the change in the shape of the building without changing the building mass. Meanwhile, from the linkage typology, there is no change in the road network pattern from the 4 study year periods. Changes in building typology in the Malioboro area tend to be close to the Beringharjo market, while there is no change in building typology for the Agung building. However, near another historical building, namely the Vredeburg fort, there are indications of an additional building mass on the east side of the building. Its also that changes in the typology of buildings in this area are influenced by the location of the building on the road class .This needs to be considered so that policy references or directions can be given to control developments in cultural heritage areas.